A Prospects for Management of Four Islands Post-Conflict in the Aceh-North Sumatra Region - Nezeliana Putri; Bambang Syaeful Hadi; Suhadi Purwantara; Pan Surya Handika; Umri Rahman Efendi (Politeknik Negeri Batam, 2026)
The resolution of the dispute over four islands—Mangkir Gadang Island, Mangkir Ketek Island, Lipan Island, and Panjang Island—between Aceh Province and North Sumatra Province marks a new chapter in post-conflict maritime governance in Indonesia. This study aims to analyze the prospects for the management of these four islands following the territorial boundary agreement reached on June 17, 2025, covering geopolitical implications, strategic potential, security stability, and opportunities for marine environmental protection. This study employs a qualitative approach using descriptive analysis through document review, spatial data interpretation based on Google Earth, and a policy review of official documents from the Ministry of Home Affairs (KEMENDAGRI), Presidential Decrees, and relevant academic literature. The results of this study identify four key post-conflict management prospects, namely: (1) collaborative management of fishery resources between the two provinces; (2) the development of marine ecotourism based on the conservation of marine biodiversity; (3) enhancing local security stability through inter-regional dialogue forums; and (4) strengthening inter-regional cooperation in the protection of coastal ecosystems and integrated marine zoning. This study contributes to the development of a post-conflict small island governance model that can be replicated to resolve similar administrative boundary disputes in Indonesia, while also strengthening a framework for sustainable, cross-provincial collaborative maritime area management.